p53 binds the mdmx mRNA and controls its translation - Tournillon, A-S; López, I; Malbert-Colas, L; Findakly, S; Naski, N; Olivares-Illana, V; Karakostis, K; Vojtesek, B; Nylander, K; Fåhraeus, R (Oncogene, 2017)
MDMX and MDM2 are two nonredundant essential regulators of p53 tumor suppressor activity. MDM2 controls p53 expression levels, whereas MDMX is predominantly a negative regulator of p53 trans-activity. The feedback loops between MDM2 and p53 are well studied and involve both negative and positive regulation on transcriptional, translational and post-translational levels but little is known on the regulatory pathways between p53 and MDMX. Here we show that overexpression of p53 suppresses mdmx mRNA translation in vitro and in cell-based assays. The core domain of p53 binds the 5' untranslated region (UTR) of the mdmx mRNA in a zinc-dependent manner that together with a trans-suppression domain located in p53 N-terminus controls MDMX synthesis. This interaction can be visualized in the nuclear and cytoplasmic compartment. Fusion of the mdmx 5'UTR to the ovalbumin open reading frame leads to suppression of ovalbumin synthesis. Interestingly, the transcription inactive p53 mutant R273H has a different RNA-binding profile compared with the wild-type p53 and differentiates the synthesis of MDMX isoforms. This study describes p53 as a trans-suppressor of the mdmx mRNA and adds a further level to the intricate feedback system that exist between p53 and its key regulatory factors and emphasizes the important role of mRNA translation control in regulating protein expression in the p53 pathway.
Keywords: nádorový supresorový protein p53; myši; messenger RNA; jaderné proteiny; protoonkogenní proteiny c-mdm2; RNA, Messenger; zvířata; Humans; Mice; Tumor Suppressor Protein p53; Proto-Oncogene Proteins c-mdm2; Nuclear Proteins; lidé; Animals